(untitled) (Research, Society and Development, 2022)
The causes of death are configured as one of the main sources to know the health status of populations and a considerable percentage of deaths classified as ill-defined compromise the quality of the data. Thus, the objective was to carry out an integrative review of published studies on mortality and the epidemiological profile of deaths from ill-defined causes. This is a literature review study. The databases consulted were PubMed, Scielo and Lilacs and the terms used were: Mortality OR Cause of death AND ill-defined, in May 2021. The eligibility criteria for selection were to be an original article; be published in Portuguese, English or Spanish; be an ecological or cross-sectional study; whether the outcome variable is the indicator of proportional mortality from ill-defined causes or the epidemiological profile of deaths from ill-defined causes. The search strategy identified a total of 1,327 publications. After removing duplicates and applying the eligibility criteria, 22 articles were included in the review. The articles were published between the years 2007 to 2020. The data collected varies from 1979 to 2018, mainly with the main rates of mortality from ill-defined causes nationally, subnationally, by states or capitals. Studies show that the percentage increases with age and proportional mortality from ill-defined causes has reduced over time in Brazil, but there are disparities between regions. In addition to a need to study in smaller geographic units such as health micro-regions and municipalities.